N,N,N′,N′-Tetrakis(2-hydroxy-5-methylbenzyl)ethane-1,2-diamine dimethylformamide disolvate - Nuan-Sheng Wang; Yong-Tao Wang; Xiu-Kai Guo; Tian-Duo Li (Acta Crystallographica Section E, 2011)
The title compound, C34H40N2O4·2C3H7NO, was synthesized by the Mannich condensation of ethanediamine, formaldehyde and p-cresol. In the crystal, the tetraphenol molecule is arranged around an inversion center. The molecule and the dimethylformamide solvate are linked through an O—H...O hydrogen bond. An intramolecular O—H...N hydrogen bond occurs in the tetraphenol molecule, which may influence the molecular confomation. Futhermore, C—H...O and π–π stacking interactions [centroid–centroid distance = 3.7081 (14) Å] stabilize the crystal packing, building a three-dimensional network.